Effectiveness of Rifampicin Chemoprophylaxis in Preventing Leprosy in Close Contacts: A Systematic Review - Rinaldhy Franatha Sembiring; Cynthia Donarta Tarigan (CV. Inara, 2026)
Leprosy (Hansen’s disease) remains a major public health problem in endemic countries, where the decline in new-case detection has been slow, suggesting ongoing transmission, particularly among household members and other close contacts who face a higher risk of disease. This study aimed to evaluate the effectiveness of rifampicin as post-exposure prophylaxis (PEP) for preventing leprosy among contacts of index cases, while also describing variations in prophylactic regimens. The review was conducted in accordance with PRISMA guidelines through literature searches in PubMed and Google Scholar using combinations of terms related to leprosy/Mycobacterium leprae and rifampicin. Study selection involved title/abstract screening followed by full-text assessment based on predefined inclusion and exclusion criteria. Six studies met the eligibility criteria; these were predominantly randomized trials and evaluated diverse interventions, including single-dose rifampicin (SDR), double-dose rifampicin PEP at 20 mg/kg (SDDR-PEP), SDR plus BCG vaccination, and enhanced prophylactic regimens under protocol evaluation, which is rifampicin–bedaquiline and PEP++ (rifampicin–clarithromycin). Follow-up durations were evenly distributed between 24 and 48 months. The synthesized evidence indicates that SDR reduces leprosy incidence primarily within the first two years (≈57%), although the protective effect tends to attenuate during years 2–4. In contrast, SDDR-PEP (20 mg/kg) was associated with a reduction in individual-level risk (IRR 0.55; 95% CI: 0.36–0.83), with stronger protection among household contacts (IRR 0.35; 95% CI: 0.15–0.82). Overall, rifampicin-based PEP appears to reduce leprosy occurrence among close contacts, particularly in the early post-intervention period; however, the magnitude of impact is influenced by transmission dynamics, the breadth of contact targeting, and the quality of screening and program implementation. Evidence for enhanced PEP regimens remains preliminary and requires definitive effectiveness results before broad recommendation.